2007
DOI: 10.1016/j.bcp.2007.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of synaptic transmission and plasticity by neuronal nicotinic acetylcholine receptors

Abstract: Nicotinic acetylcholine receptors (nAChRs) are widely expressed throughout the central nervous system and participate in a variety of physiological functions. Recent advances have revealed roles of nAChRs in the regulation of synaptic transmission and synaptic plasticity, particularly in the hippocampus and midbrain dopamine centers. In general, activation of nAChRs causes membrane depolarization and directly and indirectly increases the intracellular calcium concentration. Thus, when nAChRs are expressed on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
114
1
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(117 citation statements)
references
References 165 publications
(223 reference statements)
1
114
1
1
Order By: Relevance
“…The permeability ratio PCa/PNa, which is the relative permeability of calcium to sodium ions, was then estimated using the Goldmann-Hodgkin-Katz constant field equation [16,17] . The PCa/PNa ratio estimated in this way was ~2 for heteromeric neuronal non-α7 nAChRs, and >10 for homomeric α7 or the heteromeric α9/α10 nAChRs [2,3,7,8] . However, this relative approach has serious limitations.…”
Section: Cytoplasmic Calcium Signals Initiated By Neuronal Nachr Actimentioning
confidence: 87%
See 2 more Smart Citations
“…The permeability ratio PCa/PNa, which is the relative permeability of calcium to sodium ions, was then estimated using the Goldmann-Hodgkin-Katz constant field equation [16,17] . The PCa/PNa ratio estimated in this way was ~2 for heteromeric neuronal non-α7 nAChRs, and >10 for homomeric α7 or the heteromeric α9/α10 nAChRs [2,3,7,8] . However, this relative approach has serious limitations.…”
Section: Cytoplasmic Calcium Signals Initiated By Neuronal Nachr Actimentioning
confidence: 87%
“…The nAChRs are widely expressed in the brain, located both at the synapse (presynaptically and postsynaptically) as well as extrasynaptically [1,2] . Presynaptic and preterminal nAChRs can enhance neurotransmitter release, postsynaptic nAChRs can contribute to fast excitatory transmission, and extrasynaptic nAChRs can modulate many neurotransmitter systems by influencing neuronal excitability and/or intracellular processes [1][2][3] . The nAChRs play important modulatory roles in neuronal development and synaptic plasticity, participating in cognitive functions such as learning, memory, and attention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuronal nAChRs are ligand-gated, cation-permeable channels that are assembled in pentamers composed in a variety of subunit combinations (␣2-␣10 and ␤2-␤4; (Dani, 2001;Barik and Wonnacott, 2009), with the ␣4* bearing nAChR being the most prevalent (* indicates that there are other subunits in the pentameric nAChR). Studies have shown that nAChRs can regulate synaptic plasticity in the hippocampus and reward pathways (McKay et al, 2007;Nashmi et al, 2007;Changeux, 2010). In the visual cortex, these receptors are highly expressed during the critical period of ocular dominance plasticity (Prusky et al, 1988), which can be extended by removing a molecular brake on nAChR function (Morishita et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…7 The nerve terminal is a potential site of action for anaesthetic effects on synaptic transmission. 8 Selective inhibition of depolarization-evoked release of excitatory glutamate vs release of inhibitory GABA from neocortical nerve terminals by clinically relevant concentrations of IAs supports an overall depression of excitatory transmission during anaesthesia.…”
mentioning
confidence: 99%